Teledermatopathology on the ADOI platform and beyond - Cesare Massone; Antonio Perasole; Luigi Naldi (PAGEPress Publications, 2023)
In September 2021 on the platform of the Italian Association of Hospital Dermatologists (ADOI; https://www.adoi.it/) a monthly on-line live session of teledermatopathology was started involving collegial discussion among experienced Italian pathologists about challenging melanocytic tumors using the virtual microscope [...].